ANALISIS TANDA VISUAL DALAM TAGAR CORONA ART MUSEUM - Nofrizaldi, Nofrizaldi; Arifianto, Pungky Febi; Pertiwi, Elianna Gerda (Institut Bisnis dan Teknologi Indonesia, 2020)
The gallery is a space of interaction between artists and audiences. In the era of pamdemik covid, gallery space was closed due to physical distancing. Imaginary space is built by utilizing communication and information technology. Instagram as a digital platform is widely used as a space for building artistic interactions. Through the hashtag of Corona Art Museum, the writer looks for some visual works to be used as object of analysis. Verbal and visual signs in the visual content will be dissected using the classification of signs: icons, indexes, symbols from Charles S. Peirce and the system of meaning production of codes using The Five Code: Hermeunetic, Narrative, Cultural, Semantik & Symbolic from Roland Barthes. The reading of visual signs will use the Sumbo Tinarbuko Triadik in looking at aspects of visual communication. The results of reading visual signs will reveal how visual content in an imaginary space can be a space of expression and the existence of an artist / designer.